Primary School Curriculum Reform in Türkiye: Analyzing Recent Innovations in National Education Policies - Gürhan, Ethem (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
Türkiye has recently reformed its curriculum to emphasize 21st-century skills, integrating critical thinking, digital literacy, and values education. These efforts culminated in the 2023 Turkish Century Maarif Model, which balances modernization, national identity, and global frameworks like the OECD Learning Compass and UNESCO’s Education for Sustainable Development Goals. This study aims to critically analyze the key features, implementation strategies, and practical implications of the Turkish Century Maarif Model within the context of global frameworks such as the OECD 2030 Learning Compass and the Sustainable Development Goals. Using qualitative research design, the study employed document analysis and thematic content analysis to examine official policy papers, national education reports, and peer-reviewed literature published between 2018 and 2024. Findings indicate that while the reform promotes innovation, digital literacy, and student-centered pedagogy, several systemic barriers persist. These include inadequate teacher training, regional disparities in educational infrastructure, and misalignment between assessment systems and new pedagogical goals. Bridging the gap between policy and practice requires inclusive teacher professional development programs, equitable investment in digital infrastructure, and a restructured assessment framework that supports competency-based learning.